Financial Planning Literacy Education in Correctional Institutions Cape Leprosy I Medan - Bayu Wulandari; Namira Ufrida Rahmi; Jessi Charina Sembiring; Thomas Firdaus Hutahaean (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community Service Activities at the Medan Class I Correctional Institution, aim to increase the understanding of financial literacy in inmates in Class I prisons in Medan. This is done because financial literacy is very important to understand and apply in life so that the inmates have an understanding of financial literacy that can be used not only now, but even later in personal/family finances. The method used is socialization by providing motivation with lectures and discussions in the form of question and answer sessions. The results of community service show that financial literacy is still a new knowledge for some inmates. Although positive financial literacy greatly influences financial behavior and financial management itself. By participating in this activity, it is hoped that it will increase financial literacy, and have an impact on good financial management and avoid various financial crimes. In this case make presentations with various themes related to finance.